2003
DOI: 10.24200/jams.vol8iss1pp35-40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Concentrations of Growth Regulators on Gardenia jasminoides cv. Veitchii Micropropagation by Tissue Culture Technique

Abstract: Micropropagation techniques were set up for Gardenia jasminoides c.v. veitchi. Many plantlets were obtained by culturing shoot cuttings in MS nutrient media, 30 g/L Sucrose, 7 g/L Agar Agar, and different concentrations of BAP and IAA. The best concentration was 1mg /L BAP with 0.5 mg/L IAA. This concentration gave the best sprout growth suitable for rooting in primary and secondary culture by reculturing the stuck cutting every 6 weeks and for many times. We also obtained a high rooting percentage up to 98 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It attributes to the fact that IBA is one of the auxins that encourages cell division and elongation, then stimulates the formation of roots from the cut areas, increasing the concentration of growth regulators, which leads to an enhancement in the root number and length to reach the optimum values. However, the higher concentration of auxins may lead to the inhibition of root initiators and reduce their number (Hartmann et al, 2010;Abdullah et al, 2003). Previous research also described the process of roots and sprouting shoots throughout the stage of multiplication for the Digitalis lanata plant (Ghanem et al, 2010) and Catharanthus roses in vitro (Al-Mukhtar and Muslim, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It attributes to the fact that IBA is one of the auxins that encourages cell division and elongation, then stimulates the formation of roots from the cut areas, increasing the concentration of growth regulators, which leads to an enhancement in the root number and length to reach the optimum values. However, the higher concentration of auxins may lead to the inhibition of root initiators and reduce their number (Hartmann et al, 2010;Abdullah et al, 2003). Previous research also described the process of roots and sprouting shoots throughout the stage of multiplication for the Digitalis lanata plant (Ghanem et al, 2010) and Catharanthus roses in vitro (Al-Mukhtar and Muslim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The gardenia is one of the indoor plants that bloom abundantly with everlasting greenery, grown inside buildings, balconies, and shaded home gardens, and serves as a valuable breeding plant. However, few varieties can stay outside because of their sensitivity to high summer heat and direct sunlight (Abdullah et al, 2003). Also very popular for its beautiful flowers and aromatic scent, its economic importance relates to its use in the perfume and dye industries because of its crocetin content (Phatak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bader et al (2000) found that perfect rooting (100%) can be obtained at growth shoot culture with pear stock (Pyrus calleryana) in multiplication stage on MS medium half strength with 6.66 Mm NAA which gave 2.7 root/shoot. Abdullah et al (2003) stated that many plantlets were obtained by culturing shoot cuttings of Gardenia in MS nutrient media with 30gl -1 sucrose, 7 gl -1 agar and different concentrations of BA and IAA .The best combination was 1mgl -1 BA with 0.5mgl -1 IAA. This treatment gave the best shoot growth suitable for rooting in primary and secondary culture by reculturing the rootstock cutting every 6 weeks and for many times.…”
Section: Introductionmentioning
confidence: 99%